The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jhydrol.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide regional flood frequency analysis at ungauged sites using ROI/GLS with copulas and super regions

Abstract: Region of influence is a common approach to estimate runoff information at ungauged locations. To estimate flood quantiles from annual maximum discharges, the Generalized Least Squares (GLS) framework has been recommended to account for unequal sampling variance and intersite correlation, which requires a proper evaluation of the sampling covariance structure. Since some jurisdictions do not have clear guidelines to perform this evaluation, a general procedure using copulas and a nonparametric intersite correl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Clusters 4 and 5 show a large negative BIAS and cluster 5 shows a very large negative RBIAS. The results here are notably higher than those reported in Durocher et al [67], Chokmani and Ouarda [68], Chebana et al [47], and Shu and Ouarda [69]. In Rahman et al [6], independent component regression was adopted to develop flood prediction equations using the same data set as of this study, where error values are similar to this study.…”
Section: Development Of Prediction Equation and Performance Testingsupporting
confidence: 65%
See 2 more Smart Citations
“…Clusters 4 and 5 show a large negative BIAS and cluster 5 shows a very large negative RBIAS. The results here are notably higher than those reported in Durocher et al [67], Chokmani and Ouarda [68], Chebana et al [47], and Shu and Ouarda [69]. In Rahman et al [6], independent component regression was adopted to develop flood prediction equations using the same data set as of this study, where error values are similar to this study.…”
Section: Development Of Prediction Equation and Performance Testingsupporting
confidence: 65%
“…These studies were carried out using ordinary kriging in PCA-space, generalized additive model and single artificial neural network. Studies carried out by Durocher et al [67], Chokmani and Ouarda [68], Chebana et al [20] and Shu and Ouarda [69] show RBIAS values ranging from −5% to −20% for 10% AEP flood and −7% to −27% for 1% AEP flood. A study carried out by Rahman et al [6] found RBIAS values ranging from 22% to 69% for the six AEP floods.…”
Section: Development and Testing Of Regression Equation In Fixed Regimentioning
confidence: 92%
See 1 more Smart Citation
“…The hydrological neighborhood‐based method is gaining popularity due to its improved performance and flexibility in selecting sites (Ouarda, ; Ouarda et al, ). CCA (Ouarda et al, ) and the region of influence (ROI) (Burn, ; Burn, ; Durocher et al, ; Haddad & Rahman, ) are among others commonly utilized and reliable approaches in the delineation of homogeneous regions. Table summarizes a few commonly utilized methods of delineating homogeneous regions.…”
Section: Introductionmentioning
confidence: 99%
“…Within this network, Sandink et al and Zahmatkesh at al. [23,24] examined FFA using a quantile regression model that considered ungauged catchments across Canada. Zhang et al [39] demonstrated the generalized extreme value (GEV) distribution fits Canadian annual maximum flow data considerably better than other well-known distributions, including generalized logistic, Pearson type III, and log Pearson type III distributions.…”
Section: Introductionmentioning
confidence: 99%